Analisis Strategi Manajemen Perubahan Untuk Meningkatkan Daya Saing Toko Harian Amrizal Lubuk Begalung - Mahendra, Adiprana; Dela, Mutiara; Rahmi, Silvi Nur; Vanilia, Viola Sisi; Putra, Ramdhani Bayu (CV. ITTC INDONESIA, 2024)
The Amrizal Daily Shop in Lubuk Begalung, Padang City, faces challenges in maintaining competitiveness amidst increasingly competitive market dynamics. This research aims to design an effective change management strategy to increase store competitiveness. A qualitative descriptive approach was used in this research, with data collection methods in the form of interviews, observation and document analysis. The research results show that the success of change management depends on five main aspects: analysis of the internal and external environment, establishing a clear change vision, employee empowerment, use of digital technology, and customization of customer service. Implementation of this strategy succeeded in increasing operational efficiency, customer satisfaction and the store's competitive advantage. With a planned strategy and active participation from all parties, Toko Harian Amrizal can adapt to market changes and create added value for customers.